Gradual, temperature-induced change of secondary sexual characteristics in Trichogramma pretiosum infected with parthenogenesis-inducing Wolbachia - Ning,Su-fang; Zhou,Jin-cheng; Liu,Quan-quan; Zhao,Qian; Dong,Hui (PeerJ, 2019)
Intersex is an intermediate stage of sexual differentiation in insects. Determining intersex morphology and the cause of its production will aid in the understanding of the mechanism of sexual differentiation in insects. In this paper, Wolbachia-infected Trichogramma pretiosum (T. preW+) that shows thelytokous parthenogenesis were used as subjects. In order to determine the causes of the T. preW+ intersex and the influence of parental generation temperature on gradual changes in secondary masculinization in intersex offspring, we examined the occurrence of intersex offspring (F1 and F2 generation) after the parental generations were treated with high temperature (27, 29, 31, and 33 °C) and described the external morphology of the intersexes. The results showed that the T. preW+ parental generation temperature is positively correlated with the probability of intersex offspring. The probability of F1 intersex is significantly higher than that of F2 intersex in different high temperature. The degree of secondary masculinization in T. preW+ intersexes increases as parental generation temperature increases. In addition, our study first identified 11 intersex types in T. preW+ and found that the primary and secondary sexual characteristics showed a regular distribution. We also found that the D type and H type of intersex have the highest frequency of appearance. The external genitalia of most intersexes were female, and only three intersex types have male external genitalia. Conclusions were ultimately obtained: Wolbachia is a direct factor that causes the occurrence of intersexes, while high temperature is an indirect factor that determines the external morphology of intersexes. The effects of high temperature on T. preW+ intersexes is passed through the parental generation to offspring, and this maternal effect weakens as the number of generations increases. In T. preW+ intersex individuals, most exhibit female primary sexual characteristics, and secondary sexual characteristics exhibit signs of masculinization.
Keywords: Trichogramma pretiosum; Temperature; Wolbachia; Intersex; Secondary sexual characteristics